Promoting Safety Through Law, National and International, and by Other Means - Keith, Ken J (Victoria University of Wellington Law Review, 2018)
The Woodhouse family, friends of Sir Owen Woodhouse and the law faculties of the Victoria University of Wellington and the University of Auckland decided on the occasion of what would have been Sir Owen Woodhouse’s 100th birthday that a fellowship and lectureship should be established in recognition of the great contributions he has made to law and policy in New Zealand and beyond. The fellows and lecturers are not to see themselves as limited to the law and are encouraged to address broader matters challenging people here and abroad. Sir Kenneth Keith gave the inaugural Sir Owen Woodhouse Memorial Lecture in Wellington on 29 August 2017 and in Auckland on 30 August 2017. The address considers in turn the dangers and perils at work, at sea and on the battlefield. It reflects on New Zealand’s accident compensation scheme and suggests possible extensions to the scheme.